Survey of magnetic reconnection signatures in the Martian magnetotail with MAVEN. Issue 5 (9th May 2017) - Harada, Y.; Halekas, J. S.; McFadden, J. P.; Espley, J.; DiBraccio, G. A.; Mitchell, D. L.; Mazelle, C.; Brain, D. A.; Andersson, L.; Ma, Y. J.; Larson, D. E.; Xu, S.; et al.
Abstract: We conduct an extended survey of reconnection signatures observed in the Martian magnetotail by the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission. Although it is well established that magnetic reconnection plays a fundamental role in the dynamics of intrinsic magnetospheres, the role of reconnection in the dynamics of induced magnetospheres remains poorly understood. Based on comprehensive plasma and field measurements by MAVEN in the Martian magnetotail, we first identified 776 current sheet crossings and then selected 34 crossings with Hall magnetic field signatures, which are indicative of the ion diffusion region of tail reconnection. For the majority of the identified Hall field events, we observe ion flow enhancements in the directions consistent with the reconnection outflow directions expected from the Hall magnetic field polarity. The reconnection signatures are preferentially observed in the − E hemisphere of the near‐Mars magnetotail at ∼1–2 Mars radii downstream from Mars. We have found no strong correlation of the likelihood of observing reconnection signatures with local crustal field strengths or with upstream drivers. The duty cycle of tail reconnection is estimated to be ∼1–10% or even higher. The MAVEN observations suggest that magnetic reconnection can play an important role in the dynamics of the Martian magnetotail. Key Points: First extended survey of comprehensive in situ reconnection signatures in the Martian magnetotail Reconnection occurs preferentially in the − E hemisphere of the near‐Mars magnetotail Reconnection could operate for at least 1‐10% of the time in the Martian magnetotail